Patients' maximum acceptable waiting time for cataract surgery: a comparison at two time‐points 7 years apart. Issue 1 (30th March 2017) - Weingessel, Birgit; Wahl, Michael; Vécsei‐Marlovits, Pia V.
Abstract: Purpose: To evaluate the maximum acceptable waiting time (MAWT) of cataract patients and assess the determinants of their perception of MAWT at two time‐points 7 years apart. Methods: In 2007 (prior to the transformation of our cataract service to a day case unit) and 2014, 500 consecutive patients with cataract were asked to fill in a preoperative questionnaire addressing their MAWT to undergo cataract surgery. The patients' visual impairment (VF‐14 score), education and social status were evaluated. Results: The mean MAWT was 3.2 months in both periods, whereas the actual waiting time decreased significantly by 1.7 months (p < 0.001). Patients who had self‐noted visual impairment were nearly four times (p < 0.001) more likely to accept only an MAWT of <3 months in 2007. In both periods, patients with a VF‐14 score lower than the mean were more likely to accept a shorter MAWT (p = 0.002 and p = 0.034). Living together with children or having relatives close by was associated with a greater acceptance of an MAWT longer than 3 months (p = 0.002 and p = 0.023). Conclusion: Reducing the actual mean waiting time had no impact on the mean MAWT. Patients with poor tolerance of waiting had greater self‐reported difficulty with vision. Social support was also a strong predictor from the patients' perspective. The VF‐14 score had a greater impact than clinical visual acuity (VA) testing. Considering the implementation of standards for waiting lists, objective criteria to guarantee a transparent system should be taken into account.